ترجمة الشيخ نوويّ البنتاني و تفسيره (State Islamic University (UIN) of Sunan Ampel Surabaya, 2010)
Shaykh Nawawi (1815-1897 M) is a scholar (ulama) and great author. This scholar has a high intellectual reputation in international domain. He lived and stayed in Mecca to learn and, all at once, teach Islam. Beside that, he is an Indonesian scholar that has sufficiently great merit in developing Islamic missionary endeavor. He had written more than 100 books of Islamic tenet consisting of tafsir, tasawwuf and akhlaq, fiqh, Islamic theology, Arab language and hadith. His books, beside they are studied by Arabic community in Middle East, are studied by people in Egypt, Malaysia, and Indonesia. His popularity made his name written in al-Munjid, a popular and most completed Arabic dictionary. Furthermore, he was also awarded a title as Sayyid `Ulama' Hijaz (Leader of Hijaz Scholar)